The Trend of Using Smart Apps Creator as an Interactive Learning Media: a Literature Review - Rahmawati, Diya Rofika; Yuliyanto, Riyan (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2024)
This research article aims to summarize the results of research related to smart apps creator (SAC) as an interactive learning medium so that it becomes a reference for educators who want to implement SAC into learning. The method used is a literature review sourced from national and international journals, and scientific articles from the conference proceedings. There are four focuses of discussion in this article, namely (1) The viewpoint according to learners in using SAC learning media, (2) The advantages and disadvantages of SAC as a learning medium, (3) The process of compiling materials into SAC applications with the ADDIE development model, and (4) The appropriateness of SAC as an interactive learning media. The findings from existing research show that educators must pay attention to the needs of students in learning activities because they need devices with a lot of RAM storage and teachers must buy licenses.